The human kinesin‐14 HSET tracks the tips of growing microtubules in vitro. Issue 9 (8th October 2013) - Braun, Marcus; Lansky, Zdenek; Bajer, Seweryn; Fink, Gero; Kasprzak, Andrzej A.; Diez, Stefan
<x xml:space="preserve">Abstract</x> Tip‐tracking of kinesin‐14 motor proteins is believed to be crucial for the assembly and maintenance of dynamic microtubule arrays. However, in contrast to other members of the kinesin‐14 family, H. sapiens kinesin‐14 HSET has so far never been observed to be prominently located at microtubule plus ends. Here, using an in vitro microtubule dynamics reconstitution assay we observe tip‐tracking of GFP‐HSET in the presence of H. sapiens EB1 (hsEB1). Tip‐tracking depended on the SxIP‐like motif in HSET as well as on the EB homology domain in hsEB1. D. melanogaster Ncd and S. pombe Klp2 tip‐tracking reconstitution assays accompanied by kinesin‐14 amino acid sequence comparisons suggest that SxIP‐like motif mediated tip‐tracking dependent on EB family proteins is conserved in the kinesin‐14 family of molecular motors. © 2013 Wiley Periodicals, Inc.